Effects of volume change and boundary condition on desiccation crack network of initially slurried soils - Ng, San San. (2011)
Desiccation cracking affects the overall strength and stability of soil. This is because the presence of cracks due to the desiccation process creates zones of weaknesses in the soil. As a result, this might lead to various problems such as slope stability and bearing capacity of foundations.